Strategi Kolaborasi Key Opinion Leader dalam Membangun Brand Awareness Herbakof melalui Event Ramadan - Hermin Kusumajati; Jasmin Jannatania (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2026)
Digital media growth has encouraged brands to adopt more relevant, personal, and interactive marketing communication strategies. One approach is collaboration with Key Opinion Leaders (KOLs), particularly during cultural and seasonal campaigns such as Ramadan. This study examines Herbakof’s KOL collaboration strategy in building brand awareness through a Ramadan event campaign. A descriptive qualitative approach was used to explore campaign planning, implementation, audience engagement, and post-event communication. Conducted over six months, the study involved three informants selected based on their roles in the campaign. Data were collected through in-depth interviews, event observation, and documentation of campaign content. The findings show that KOL collaboration supported not only message dissemination but also meaningful relationships between the brand and its audience. Effectiveness depended on KOL credibility, character compatibility, campaign messages, event context, audience experience, and post-event communication. The study contributes to branding theory by explaining how KOL collaboration and event experiences strengthen brand awareness.